Endoscopic papillary balloon dilatation may preserve sphincter of Oddi function after common bile duct stone management: evaluation from the viewpoint of endoscopic manometry. Issue 4 (1st October 1997) - Sato, H; Kodama, T; Takaaki, J; Tatsumi, Y; Maeda, T; Fujita, S; Fukui, Y; Ogasawara, H; Mitsufuji, S
Abstract : Background —Endoscopic papillary balloon dilatation (EPBD) has been reported as a safe and effective alternative to endoscopic sphincterotomy in the management of common bile duct (CBD) stones; its effect on papillary function has yet to be elucidated. Aim —To investigate sphincter of Oddi (SO) motility before and after EPBD to determine its effect on SO function. Patients and methods —The papillary function of 10 patients with CBD stones was studied using endoscopic manometry before and one week after EPBD. The manometric studies were repeated one month after EPBD in seven patients. Results —One week after EPBD, CBD pressure, SO peak pressure, SO basal pressure, and SO frequency decreased significantly. One month after EPBD, however, all parameters increased although the increases in SO basal pressure and CBD pressure were not significant. There was no significant difference in values of any parameter before and one month after EPBD. No serious complications occurred. Conclusion —These data suggest at least partial recovery of papillary function one month after the procedure. EPBD seems to preserve papillary function in treatment of CBD stones; a longer term follow up study with SO manometry should be performed to clarify the effect of EPBD on SO function.